Molecular dynamic simulation of nanocrystal formation and tensile deformation of TiAl alloy. Issue 76 (16th October 2017) - Li, Peng-tao; Yang, Yan-Qing; Xia, Zhenhai; Luo, Xian; Jin, Na; Gao, Yong; Liu, Gang
Abstract : The formation of BCC structure in the melt was the key in TiAl crystalline nucleation, and liquid TiAl alloy completely crystallized at the quenching rate of 0.02 K ps −1 . Abstract : The formation of nanocrystals from undercooling TiAl melt and deformation behavior of nanocrystalline TiAl alloy under tensile loading conditions are investigated by molecular dynamics simulation. The effects of quenching rate related to the solidification structure evolution during rapid quenching are described by internal energy, radial distribution functions, and common neighbor analysis. The simulation results indicate that the accumulation of atoms with icosahedral configuration and transformation into atomic cluster with BCC configuration in the undercooling melt are the key in crystalline nucleation growth, and eventually liquid TiAl alloy completely crystallizes at the quenching rate of 0.02 K ps −1 . In the tensile deformation, grain boundaries sliding and lamellar domain increasing are the two main deformation mechanisms during plastic deformation, and cracks form due to the nucleation, growth and coalescence of void along the grain boundaries, which results in subsequent failure in nanocrystalline TiAl alloy. This paper provides fundamental understanding of the nanocrystalline formation of undercooling TiAl melt and the deformation mechanisms in the nanocrystalline TiAl at the atomic scale.